Modeling Biogenic Volatile Organic Compounds Emissions and Subsequent Impacts on Ozone Air Quality in the Sichuan Basin, Southwestern China - Zhang, Shaobo; Lyu, Yaqiong; Yang, Xianyu; Yuan, Liang; Wang, Yurun; Wang, Lei; Liang, Yuxin; Qiao, Yuhong; Wang, Shigong (Frontiers in Ecology and Evolution, 2022)
Biogenic volatile organic compound (BVOC) impacts atmospheric oxidation capacity and regional air quality through various biogeochemistry processes. Accurately estimation of BVOC emissions is crucial for modeling the fate and transport of air pollutants in chemical transport models. Previous modeling characterizes the spatial variability of BVOC while estimated BVOC emissions shows large uncertainties and the impacts of BVOC emissions on ozone (O3) air quality are not well understood. In this study, we estimate the BVOC emissions by Model of Emissions of Gases and Aerosols from Nature (MEGAN) v2.1 and MEGANv3.1 over the Sichuan Basin (SCB) situated in southwestern China for 2017. Further, the critical role of BVOC emissions on regional O3 pollution is illustrated with CMAQ modelled O3 episode in summer 2017. Annual BVOC emissions over the SCB in 2017 are estimated to be 1.8 × 106 tons with isoprene emission as high as 7.3 × 105 tons. Abundant BVOC emissions are depicted over southern and southeastern SCB, in contrast to the relatively low emissions of BVOC over Chengdu Plain and northeastern SCB. CMAQ simulations depict strong influence of BVOC on ambient O3 formation over densely forested regions including southern SCB and Chongqing city, accounting for 10% of daily max hourly O3 concentration (DM1h O3) and 6% of daily maximum 8-hour average O3 (MDA8h O3) concentrations in July 2017. Over the severe O3 episode in summer 2017, sensitivity experiments indicate that enhanced BVOC emissions contribute substantially to basin-wide O3 concentrations and elevate peak O3 levels by 36.5 μg/m3 and 31.2μg/m3 for southern SCB and Chengdu Plain, respectively. This work identifies robustly important effects of BVOC emissions on O3 exceedance events over the SCB and contributes insight into pursuing an O3 abatement strategy with full consideration of potential contribution from BVOC emissions..